Actividad conservante de extractos de propóleo, canela y clavo de olor encapsulados, en una bebida funcional de avena y camote - Mera Sabando, Paola Estefanía (2025)
This study aimed to evaluate the preservative activity of encapsulated extracts of propolis, cinnamon, and clove in a functional beverage made from oats and sweet potato. Six treatments were prepared using two encapsulation methods (ionic gelation and spray drying) and a control with potassium sorbate, stored at 4 °C for 60 days. Microbiological analysis, acidity, pH, antioxidant capacity, and phenolic content were assessed on days 0, 20, 40, and 60. Treatment T6 (clove extract encapsulated by spray drying) showed the best microbiological results, maintaining Escherichia coli and coliform counts below 10 UFC, according to NTE INEN 2564 standards. Antioxidant capacity increased from 125.78 to 436.50 μMol Trolox equivalent/100 mL between days 21 and 30, highlighting the delayed release of active compounds. Conversely, treatments T2 (propolis) and T4 (cinnamon) exhibited higher initial values (up to 215.37 μMol TE/100 mL) but decreased by day 30. The phenolic content of treatment T6 decreased from 356.94 to 34.09 mg GAE/100 mL over the same period, attributed to oxidation and degradation processes. Microbiological contamination detected in other treatments was linked to post-pasteurization failures. Microencapsulated clove extract by spray drying proved to be the most efficient treatment for preserving the functional beverage, ensuring microbiological quality and antioxidant stability during storage.